Lomba Cerdas Cermat Sebagai Metode Inovatif Pengembangan Minat Belajar Siswa SDN Kalisari 1 Surabaya - Ramadhani, Achmad Nur; Sitanggang, Klose Margaret Oktavia; Cahyani, Astri; Rizky, Muhammad Alfafa; Harianto, Saefudin Fajar; Rahmatin, Leily Suci (Universitas Nusantara PGRI Kediri, 2024)
The digital era has brought the challenge of declining interest in learning among elementary school students. To overcome this, innovative learning methods are needed that can increase student learning motivation. This service aims to increase learning interest, knowledge, and academic skills of 4th grade students at SDN Kalisari 1 Surabaya. This activity uses a case study method, data is collected through direct observation during the competition and interviews with homeroom teachers. Results showed that the quiz competition effectively increased students' learning motivation, academic knowledge and critical thinking skills. This activity also encourages achievement, increases self-confidence, and develops quick and precise thinking skills. This method has the potential to be an innovative learning strategy that can be implemented by SD Negeri Kalisari 1 Surabaya.